2002
DOI: 10.1074/jbc.m111357200
|View full text |Cite
|
Sign up to set email alerts
|

Src-mediated Inter-receptor Cross-talk between the Na+/K+-ATPase and the Epidermal Growth Factor Receptor Relays the Signal from Ouabain to Mitogen-activated Protein Kinases

Abstract: Binding of ouabain to Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
265
2
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 264 publications
(292 citation statements)
references
References 24 publications
21
265
2
4
Order By: Relevance
“…Previous reports as well as our current study (Figures 2a-c) suggest that the binding of ouabain or TCTP to the Na,K-ATPase a subunit stimulates Src-mediated EGFR phosphorylation, resulting in phosphorylation of other tyrosine residues on EGFR independent of serum (Haas et al, 2002;Kometiani et al, 2005;Kim et al, 2009). Phosphorylation of Tyr992 on EGFR has been reported to result in activation of PLC-g-mediated downstream signaling (Emlet et al, 1997) and phosphorylation of a pair of tyrosines 1148 and 1173, providing a docking site for scaffold proteins such as Shc, involved in the MAP kinase signaling pathway (Zwick et al, 1999).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous reports as well as our current study (Figures 2a-c) suggest that the binding of ouabain or TCTP to the Na,K-ATPase a subunit stimulates Src-mediated EGFR phosphorylation, resulting in phosphorylation of other tyrosine residues on EGFR independent of serum (Haas et al, 2002;Kometiani et al, 2005;Kim et al, 2009). Phosphorylation of Tyr992 on EGFR has been reported to result in activation of PLC-g-mediated downstream signaling (Emlet et al, 1997) and phosphorylation of a pair of tyrosines 1148 and 1173, providing a docking site for scaffold proteins such as Shc, involved in the MAP kinase signaling pathway (Zwick et al, 1999).…”
Section: Discussionsupporting
confidence: 80%
“…Also, ouabain-induced activation of EGFR is known to induce different downstream signaling events through binding to adaptor proteins (Haas et al, 2002). Therefore, we investigated whether TCTP-induced EGFR transactivation stimulates downstream signaling pathways different from those induced by ouabain.…”
Section: Tctp-induced Src Activation Mediates Egfr Transactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis showed that ouabain increased the amount of coprecipitated Na/K-ATPase in a time-dependent manner ( Figure 3D). We showed previously that Src activation and recruitment to the signaling Na/K-ATPase is essential for ouabain to evoke downstream cascades (Haas et al, 2002). To address the role of Src in the ouabain-induced recruitment of PLC-␥1, we first probed for Src in the above immunoprecipitates, showing that ouabain stimulated the formation of the Na/KATPase/Src/PLC-␥1 complex ( Figure 3D).…”
Section: Ouabain-activated Na/k-atpase Signaling Complex Can Recruit mentioning
confidence: 94%
“…Recent work from several laboratories indicates that the enzyme also functions as a signaltransducing receptor for both endogenous and exogenous cardiotonic steroids such as ouabain (Kometiani et al, 1998;Xie et al, 1999;Haas et al, 2000Haas et al, , 2002Liu et al, 2000;Aizman et al, 2001;Aydemir-Koksoy et al, 2001;Miyakawa-Naito et al, 2003). First, binding of ouabain to the signaling Na/KATPase activates multiple signaling pathways and regulates transcription and translation of many genes in cardiac myocytes and other cell types.…”
Section: Introductionmentioning
confidence: 99%